Pembelajaran Makhārij Al-Ḥurūf di Desa Rongdurin Kecamatan Tanah Merah Bangkalan - Islamiyah (Jurnal Insan Pengabdian Indonesia, 2023)
A student, child and teenager, especially in Rongdurin Tanah Merah village, must have the ability to read the Koran rhetorically. One way is by studying Makhārij al-Ḥurūf. Because by studying and developing this knowledge, they can understand the most basic things about the hijaiyah letters. So that it can lead them to have the ability to read the Koran well. The formulation of the problem that will be raised in this activity is: "what is the urgency of training and learning Makhārij al-Ḥurūf for the children and teenagers of Rongdurin village". This program is implemented using the method of providing materials, roleplay, games and training. It is hoped that participants can receive the material well and practice directly with the assistance of the facilitator team. Implementation includes (1) Preparation, (2) Planning learning methods, (3) Subject approach, (4) Implementation of training, (5) Evaluation. The conclusion of this community service is the increasing ability of the teenagers and children of Rongdurin Tanah Merah village in understanding and exploring Makhārij al-Ḥurūf. So that children and teenagers who take part in this program can read the hijaiyah letters in the Koran properly and correctly so that the meaning is not missed or mistaken.